2022
DOI: 10.15581/003.35.2.89-106
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organizational communication, leadership, and employee commitment in organizational change in the hospitality sector

Abstract: The purpose of this study was to empirically analyze the interrelationships among organizational communication, leadership, and employee commitment, in terms of organizational change. A structural model was developed to delineate the interactions between the constructs, and to explore the mediating effects of leadership and employees’ commitment on the relationship between communication and organizational change. A quantitative online survey was conducted, based on a sample of 335 employees from the hospitalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The results confirm that COL plays a substantial role in the enhancement of employees' change commitment, which is consistent with the findings of. 11,24,32 A COL, such as depicting a vision for the future with lucid details, can help guide employees as organizations undergo change. When employees perceive COL, they have a sense of belonging and identification that increases their willingness to be involved in the organization's activities, pursue the organization's goals, and remain with the organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results confirm that COL plays a substantial role in the enhancement of employees' change commitment, which is consistent with the findings of. 11,24,32 A COL, such as depicting a vision for the future with lucid details, can help guide employees as organizations undergo change. When employees perceive COL, they have a sense of belonging and identification that increases their willingness to be involved in the organization's activities, pursue the organization's goals, and remain with the organization.…”
Section: Discussionmentioning
confidence: 99%
“…A leader's change-oriented vision might have a positive indirect relationship with employees' change commitment. 11,24 In other words, the ability of the leader to deliver this vision is also predicted to have a positive indirect relationship with change commitment. COL also encourage innovative ways to solve problems, facilitate the process of helping followers absorb new knowledge, and think "outside of the box."…”
Section: Change-oriented Leadership and Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have concluded that innovative work behavior within organizations is not only a product of individual talents and traits but also results from social and psychological influences (Khaola & Coldwell, 2019) such as commitment and willingness to share. Organizational commitment has been recognized as a crucial factor influencing employee work behavior (Hakimian et al, 2016) which contributes to the success of organizational change (Maçães & Román-Portas, 2022). Teacher commitment determines school success because it is related to creating a conducive learning environment, supporting positive behavior, and ongoing guidance.…”
Section: Introductionmentioning
confidence: 99%
“…And the capacity of a transformation leader is also confirmed to have effect on satisfaction of followers (Allozi et al, 2022;Bushra et al, 2011) and dedication (Chen & Cuervo, 2022) to the organization. Additionally, employee's self-motivation and commitment to organizational change and organizational conditions (Adnan & Azar, 2023;Herold et al, 2008;Ramos-Maçães & Román-Portas, 2022) are also affected by transformational leadership. Organizations of any kind require transformational leadership because it can positively affect success of the individual and the organization (Sharma & Jain, 2022).…”
mentioning
confidence: 99%